COUNSELING ABOUT GIVING PINEAPPLE SKIN TEA TO ELDERLY BLOOD PRESSURE WITH HYPERTENSION - bungamri sembiring; fithri handayani lubis; Bachtiyar Wahab; Bahtera Bindavid Purba (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Aging occurs when a person reaches a certain level of physical development. can change. In old age, this is the last person, who gradually degenerates physically, mentally and socially. Persistent hypertension in the arteries, with a systolic blood pressure above 140 mm Hg and a diastolic blood pressure above 90 mm Hg. The incidence of arterial hypertension increases every year. Hypertension is the most dangerous disease in the world. High blood pressure in the long term can damage various organs in the body, such as the kidneys, heart and brain. This happens if you have high blood pressure and are handled properly as soon as possible. This activity was held in Deli Tua, Deli Serdang in September 2022. All the elderly who attended this activity experienced an increase in knowledge regarding the utilization of pineapple skin waste which can be reused into tea which is beneficial for the elderly who specifically suffer from hypertension.